Report on bedding materials : Analysis of the current bedding material situation and assessment of the near-future development outlook in Finland - Manni, Katariina; Högel, Heidi; Saastamoinen, Markku; Frondelius, Lilli; Huuskonen, Arto (Natural Resources Institute Finland (Luke), 2023)
The bedding material report studied the use and availability of different bedding materials as comprehensively as possible and assessed their related future outlook and development needs in Finland. The report started from the current state of the use and availability of bedding materials. The future development outlook was assessed over a span of five years. Data collection was based on the literature, official statistics, expert assessments, and surveys conducted during the study, with one targeted at livestock producers and horse sector operators, and the other targeted at producers, sellers and/or distributors of bedding materials. To examine the regional production and use of bedding materials, Finland was divided into four major regions in accordance with the distribution of Centre for Economic Development, Transport and the Environment areas: Southern, Western, Middle and Northern Finland. Peat is a bedding material used extensively in Finland. However, it is predicted that the sales volumes of bedding peat will halve during the next five years. If this prediction is realised, new materials will urgently be required to replace and supplement peat. What makes this situation even more critical is that there is also a shortage of wood shavings and sawdust used frequently as bedding materials, at least at present, as they are used in energy generation. In addition to ensuring the availability of bedding materials, it is important to address their cost impact. As bedding is a key part of animal welfare and health, and partly of food hygiene, sufficient and effective bedding cannot be compromised. It is therefore absolutely essential to address the costs arising from bedding as well in ensuring the supply of bedding materials. To secure bedding material supply in every situation, we need to primarily ensure the availability of current and effective bedding materials, at least until they have effective options with competitive prices and sufficient availability. Launching new materials in the markets takes years, and it cannot lead to a situation where animal welfare decreases due to insufficient bedding resulting from the lower availability of bedding materials and higher prices. The selection of bedding materials is always a comprehensive farm-specific solution which is affected by the properties required from bedding materials in different situations. When comparing bedding materials, they cannot be ranked in any specific order because they have different properties, and their users’ needs also vary. Furthermore, the effectiveness of materials as a bedding material or their volumes cannot be assessed based on individual properties alone, as each bedding material needs to be considered as a whole based on several properties required of bedding materials. Peat is the most critical bedding material in broiler production. It is difficult to find a bed-ding material to replace the use of peat in broiler production to secure the high foot health and antibiotic-free production of birds. Materials that replace and supplement peat are already available for cattle, horses, sheep, and pigs. However, their sufficiency is a critical factor, as certain materials are already in short supply. Increased competition is also reflected in higher prices. This was clearly indicated by the surveys targeted as livestock producers, horse sector operators and bedding industry companies. Of biomasses produced in fields, straw is the best known and most frequently used bedding material, while not all its potential has yet been used. The use of straw could be increased in cooperation between farms and in large-scale commercial activities. Pelleted straw is good example of commercial-scale solutions, while nearly all pelleted straw is currently imported. There could therefore be potential markets for their domestic production. Increasing the use of straw in bedding materials would lead to larger harvesting areas and longer transport distances than at present. The potential of slurry and manure as bedding materials has yet to be fully utilised. The cost of separating manure produced on farms into bedding materials is not high after the initial investment. Using recycled manure as a bedding material can increase a farm’s self-sufficiency in bedding materials. Currently, solid fraction of separated slurry is only used as bedding materials for cattle. The possible use of separated manure as a bedding material for other animals as well requires research. If the use of recycled manure as a bedding material expands, sufficient quality must be maintained in all conditions. Clear guidelines should be prepared for the use of recycled manure as a bedding material to minimise risks associated with food hygiene and animal health, as has been done in the UK, for example. The significance of hygienic quality will be particularly emphasised if separated manure is transported between farms. Side streams of the wood and sawmill industry, including wood shavings and sawdust, are significant bedding materials, and their availability as such must be secured. This was a key factor last year, in particular, when competition for availability became fiercer. In addition, the use of other industrial side streams suitable for use as a bedding material should be advanced, as this also supports the circular economy. Forest industry sludge is a good example of this. The potential of natural materials, including sand, common reed, reed canary grass and peatland biomasses, as bedding materials should be studied and advanced further. Shives, by-products of the further processing of hemp fibres, can also be used as a bedding material. If domestic hemp fibre processing is scaled up, it is possible for domestic hemp-based bedding materials to be available. Currently, the use of hemp in bedding materials relies on imports. While oil hemp stems can also be used as a bedding material, their yield is not particularly high due to the harvesting methods used. Bedding material cultivation could be one way to increase the production of bedding materials. Suitable crops for cultivation include reed canary grass and willow. An increase in paludiculture would enable the cultivation of bulrush as a bedding material. Reed canary grass is also suitable for paludiculture. However, promoting bedding material cultivation calls for incentives and effective markets. Cooperation between farms is a widely used solution to secure the supply of bedding materials. Livestock and crop production farms could increase cooperation in bedding material production so that crop production farms cultivate bedding materials for livestock farms. Alternatively, livestock farms could harvest straw from crop production farms for use as a bedding, and correspondingly, cereal farms could receive straw back as manure. However, this needs incentives and good practical examples. The availability of many bedding materials must be improved significantly if their use in-creases considerably. Then again, even if the availability of a certain potential material was high, its properties might require processing. This usually increases costs and may therefore limit the use of the material. Market surveys are also needed to produce the bedding materials required and find the correct target groups for them. Options that are currently under development and testing may offer solutions for the supply of bedding materials in the future. More research and innovation, as well as courage from businesses to invest in bedding material production, are needed to produce new solutions. However, it should be noted that the development, production, and placement on the market of new bedding materials takes time – five to ten years in most cases. To make any investments in the production of bedding materials, we need incentives, including investment subsidies. The availability of current materials, especially that of peat, must be secured until proper options are genuinely available. This will ensure that livestock production and therefore the food industry do not need to be restricted due to any shortage of bedding materials. Further research into bedding material supply is required especially regarding animal farming and welfare, various uses and working methods, the costs of bedding material production and handling, and the planning of the machine chains and processes required. It is important to identify the factors that determine how the supply of bedding materials matches their demand. It should also be understood that bedding material markets that operate at different levels may be needed more in the future. Some bedding material production may be very local, including cooperation between farms, while some may be regional, and some may be national. Finding common guidelines and aiming to secure the supply of bedding materials now and in the future will be key, for which a comprehensive vision and effective interaction will be required. The various operators in the sector need to engage in even closer cooperation. If the current estimates are realised, the bedding material markets will undergo rapid change, and solutions will be required to adapt. We need not only to develop new bedding materials but also to improve the availability and resource-efficient use of wood- and peat-based bedding materials over a sufficiently long transition period to avoid the looming bedding material shortage. A roadmap to be prepared for bedding material supply by various operators in the sector is proposed as a solution so that it would define tangible short- and long-term plans to secure a sustainable supply of bedding materials.
Keywords: bedding material; bedding; peat; bedding material production; livestock production; horse husbandry; cattle; poultry; horse